Human-Large Carnivore Conflict in Nepal’s Lowland National Parks - Shah, Ganga (Journal of Physical and Life Sciences, 2024)
Human-animal conflict is one of the most widespread and urgent problems facing wildlife protection. Any direct or indirect interaction between people and animals that has an adverse effect on either party is referred to as human–wildlife conflict. Since many carnivore species have suffered greatly because of increased conflict levels with populations. Because of their extensive home ranges and food needs, which increasingly coincide with those of humans, large carnivores in particular are prone to such confrontations. A thorough search was conducted using many databases, including PNAS, Diversity and Distributions, Journal of Applied Ecology, Trends in Ecology & Evolution, The Royal Society, Diversity and Distributions, and ScienceDirect, to get studies on the human-large carnivores’ conflict in Nepal’s National Park. After a rigorous screening process, 29 articles were selected, reviewed, and analysed, published between 2014 and 2024, to determine the large carnivore species involved in conflicts and the root cause of large carnivore conflicts in lowlands of Nepal’s national park. The most popular sampling technique is the semi-structured questionnaire survey, which is followed by key informant interviews and focus group discussions. Nationally, it found that the resource collection, agricultural activities, livestock grazing, and illegal hunting near or inside parks induced the human-carnivore conflicts. The Bengal tiger and common leopard are two main carnivores engaged in conflicts. To exchange best practices and keep using innovative methods for significant human-wildlife conflict mitigation in protected areas, it is critical that various levels of government, non-governmental organizations, and civil societies work together effectively.